Impact of COVID-19 on pro- and antiatherogenic lipoproteins (cross-sectional population study) - P. S. Sadovnikov; Yu. A. Kyznetsova; P. S. Golchina; V S. Gurevich (Российский кардиологический журнал)
Aim. The aim of this cross-sectional retrospective study was to study the effect of SARS-CoV-2 S1/S2 infection on population lipid parameters, which are leading risk factors for the development and progression of atherosclerosis, which can be significantly distorted in systemic inflammation and, in particular, during respiratory viral infections.Material and methods. We analyzed anonymized results of one-time, one-year studies of complete lipid profiles and related laboratory parameters performed in the Helix Laboratory Service from February 1, 2015 to December 30, 2020 in 238541 males and 384437 females aged from 22 to 83 years in 334 populated areas of the European Russia using Roche Cobas C502, C702 (Roche Diagnostics GmbH, Mannheim, Germany), LIAISON XL (DiaSorin S.p.A, Italy) analyzers.Statistical analysis included methods of descriptive statistics, distribution analysis, sample comparisons, and search for dependencies.Results. A dramatic change in the magnitude and nature of seasonal population fluctuations in low-density lipoprotein cholesterol and high-density lipoprotein cholesterol (HDL-C) during the COVID-19 spread has been identified.COVID-19 differentially affects the relationship between high-sensitivity C-reactive protein (hsCRP) and atherogenic and antiatherogenic lipoproteins. These relationships have sex differences, are nonlinear, and in relation to HDL-C are associated with the level of specific anti-SARS-CoV-2 S1/S2 antibodies.Up to a hsCRP level of 2,5 mg/l, there is a significant increase in population levels of low-density lipoprotein cholesterol with a correlation coefficient of 0,14 for women (p<0,001) and 0,10 for men (p<0,001). At hsCRP levels >2,5 mg/l, the trend reverses. At the same time, HDL-C levels sharply decrease with a negative correlation of -0,23 (p<0,001) in women and -0,22 (p<0,001) in men with hsCRP values <2,5 mg/l, followed by a less pronounced decline.Conclusion. The study results may be useful for optimal prevention development and adequate assessment of atherogenic dyslipidemia treatment effectiveness in patients after COVID-19.